2022
DOI: 10.1021/acs.joc.2c01169
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Substituted Benzo-Fused Cyclic Sulfonamides with Mg-MeOH: An Experimental and Computational Study

Abstract: A study involving the use of Mg-MeOH for the double reductive cleavage of both N–S and C–S bonds in a series of 11 benzo-fused cyclic sulfonamides is reported. Examples where the sulfonamide nitrogen atom is part of a pyrrolidine ring effectively undergo reduction, as long as a methoxy substituent is not para -positioned in the aromatic ring, relative to the sulfonyl group. In contrast, if the nitrogen atom is contained within an aromatic ring (pyrrole or indole), the presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Deuterated solvents are commercially available, environmental benign, and easy to handle, which have been routinely used in NMR spectroscopy for the structural characterization of organic compounds . The utilization of deuterated solvents as isotope sources in deuterium-labeling reactions has also been studied. , Very recently, Ritter and co-workers reported a Pd-catalyzed homogeneous hydrogenolysis of arylthianthrenium salts with deuterium and tritium gas (Scheme ). In this article, we found that reactions of arylthianthren-5-ium salts with CD 3 OD as both solvent and deuteration reagent could allow a mild synthesis of deuterated products with high selectivity under diverse conditions.…”
mentioning
confidence: 99%
“…Deuterated solvents are commercially available, environmental benign, and easy to handle, which have been routinely used in NMR spectroscopy for the structural characterization of organic compounds . The utilization of deuterated solvents as isotope sources in deuterium-labeling reactions has also been studied. , Very recently, Ritter and co-workers reported a Pd-catalyzed homogeneous hydrogenolysis of arylthianthrenium salts with deuterium and tritium gas (Scheme ). In this article, we found that reactions of arylthianthren-5-ium salts with CD 3 OD as both solvent and deuteration reagent could allow a mild synthesis of deuterated products with high selectivity under diverse conditions.…”
mentioning
confidence: 99%